Avoidance, meaning and grief: psychosocial factors influencing engagement in HIV care. Issue 4 (3rd April 2018) - Michlig, Georgia J.; Westergaard, Ryan P.; Lam, Yukyan; Ahmadi, Azal; Kirk, Gregory D.; Genz, Andrew; Keruly, Jeanne; Hutton, Heidi; Surkan, Pamela J.
ABSTRACT: Although the introduction of antiretroviral therapy has rendered HIV a chronic illness, inconsistent engagement in HIV care by key populations limits its public health impact. Poor engagement in care is especially prevalent among vulnerable populations with mental health and substance use disorders. Beyond structural and health system considerations, psychosocial factors may present challenges to sustained engagement. We conducted a qualitative study using in-depth interviews with 31 primarily African American, urban-based individuals, many with past or current drug use and mental disorders, living with HIV. Participants identified several psychosocial barriers that detract from their motivation to attend appointments and take medication. These included mental distress or detachment over a lack of purpose in life; denial about the need to be engaged in care; insufficient trust in the efficacy of care or the health system; deaths of loved ones leading to bereavement or loss of social support; and engagement in specific avoidance behaviors like drugs and alcohol. The study findings suggest that more comprehensive HIV care, which integrates mental health and substance abuse services in order to enhance meaning and address coping and grief, may be important. Considering these services in addition to improving the logistical components of care such as cues/reminders, accessibility, and patient-provider communication may improve intervention packages.